Anteseden Urge To Buy Impulsively: Studi Empiris Pada Produk Kosmetik Yang Dijual Melalui Platform E-Commerce - Ardhevi Anggita Putri Cahyani; Kardison Lumban Batu (Faculty of Economics and Business Diponegoro University, 2025)
This study aims to empirically investigate the antecedents of the Urge To Buy Impulsively among consumers of Make Over cosmetic products on the Shopee platform in Semarang City. The research is grounded in the Commitment-Trust Theory of Relationship (Morgan & Hunt, 1994), which emphasizes the role of Trust and commitment in shaping consumer behavior. The study explores the influence of Convenience, Influencer Credibility, and Trust on the Urge To Buy Impulsively, mediated by Perceived Enjoyment and Attitude Toward Influencer Ads.The research employs a quantitative approach, utilizing Structural Equation Modeling (SEM) with data collected from 206 respondents who have purchased Make Over cosmetics on Shopee. The data were analyzed using AMOS (Analysis Moment of Structural) software to test the proposed hypotheses. The results indicate that Convenience significantly influences Perceived Enjoyment, which in turn affects the Urge To Buy Impulsively. Additionally, Influencer Credibility and Trust significantly impact Attitude Toward Influencer Ads, which also positively influences the Urge To Buy Impulsively.The findings reveal that Perceived Enjoyment and Attitude Toward Influencer Ads play crucial mediating roles in the relationship between the independent variables (Convenience, Influencer Credibility, and Trust) and the dependent variable (Urge To Buy Impulsively). Specifically, Convenience has the strongest direct effect on Perceived Enjoyment, while Attitude Toward Influencer Ads has the most substantial impact on the Urge To Buy Impulsively. The results offer practical implications for marketers and e-commerce platforms, suggesting that enhancing Convenience, building Trust, and leveraging credible influencers can effectively stimulate impulsive purchases. However, the study also highlights the need for careful management of these strategies to avoid excessive impulsive buying behavior.